Pengaruh Efektivitas Pengendalian Internal dan Kesesuaian Kompensasi terhadap Kecurangan Akuntansi: Studi Empiris pada OPD Kabupaten Solok Selatan - Febby Febiola; Vita Fitria Sari (Universitas Negeri Padang, 2024)
This studying intends to investigate and determine impact or influence of the variables on effectiveness of internal control and suitability of compensation for the accounting fraud in OPD South Solok Regency. The sampling procedure used total sampling with 32 populations, where 4 people were taken from each OPD. Multiple linear regression used in data analysis to evaluate and support the research in hypothesis. The results showed that effectiveness of internal control had a significant negative effect to accounting fraud, and suitability compensation also had significant negative effect on accounting fraud.